Local Anesthetic Systemic Toxicity during Labor, Birth, and Immediate Postpartum: Clinical Review. Issue 6 (November 2021) - Mock, Nicole D.; Griggs, Kellie M.; Mileto, Lisa A.
Abstract : Abstract: Local anesthetic systemic toxicity (LAST) is a life-threatening event caused by elevated local anesthetic plasma concentration. It is often unrecognized or misdiagnosed. Peripartum women are at increased risk for toxicity due to pregnancy-related physiological changes. Rising serum drug levels can cause cellular level impairment of mitochondria and voltage-gated ion channels leading to a cascade of symptoms that can end in cardiac arrest. Local anesthetic systemic toxicity can mimic other maternal pathologies but may be considered if local anesthetics have been used. Published treatment guidelines for this event include lipid emulsion which is approved for use in pregnant women. We review LAST in the maternity care setting, published treatment protocols, management of maternity patients with toxicity, and recommendations to increase awareness among maternity care clinicians for this medical emergency. Abstract : Local anesthetic systemic toxicity during labor, birth, and postpartum is a medical emergency requiring prompt identification and immediate resposne. A review of the pathophysiology, clinical presentation, and recommended management is provided.